2008
DOI: 10.1246/cl.2008.374
|View full text |Cite
|
Sign up to set email alerts
|

Electroluminescence Quenching Caused by a Spin-crossover Transition

Abstract: A film of a spin-crossover complex [Fe(dpp)2](BF4)2 (dpp = 2,6-di(pyrazol-1-yl)pyridine) was embedded into the light-emitting layer of an organic electroluminescent (EL) device with chlorophyll a. While the EL spectrum was observed at 300 K, the spectrum could not be observed at 200 K. The temperature dependence of the EL spectra shows the quenching of the emission below 260 K, which is the spin-transition temperature of [Fe(dpp)2](BF4)2. This suggests that the EL quenching accompanied the spin transition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(51 citation statements)
references
References 6 publications
0
48
0
3
Order By: Relevance
“…These properties have led to their incorporation into several prototype devices, including a display whose pixels are switched by spot-heating and cooling; 21 an electroluminescent device, where changes in the electrical resistance of a spincrossover thin film quench light emission from a chlorophyll dopant; 22 and, a temperature-sensitive contrast agent for magnetic resonance imaging. 23 Most real or potential applications require a material whose spin-transition occurs with a 30-50 K hysteresis loop that spans room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…These properties have led to their incorporation into several prototype devices, including a display whose pixels are switched by spot-heating and cooling; 21 an electroluminescent device, where changes in the electrical resistance of a spincrossover thin film quench light emission from a chlorophyll dopant; 22 and, a temperature-sensitive contrast agent for magnetic resonance imaging. 23 Most real or potential applications require a material whose spin-transition occurs with a 30-50 K hysteresis loop that spans room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Another approach is the doping of SCO materials with fluorescent entities, which only requires simple synthetic strategies and is capable of preserving SCO and fluorescence of two components simultaneously. For examples, Matsuda and co‐workers doped the SCO material [Fe(dpp) 2 ](BF 4 ) 2 (dpp=2,6‐di(pyrazol‐1‐yl)pyridine) with the organic electroluminescent (EL) molecule chlorophyll a in a light‐emitting layer, and found that the emission of chlorophyll a ( λ max =395 nm) was quenched below 260 K where [Fe(dpp) 2 ](BF 4 ) 2 turned to the ls state, suggesting that the EL quenching was accompanied with a SCO. The co‐crystallization doping of the SCO compound [Fe(dpp) 2 ](BF 4 ) 2 with the fluorescent [Ru(terpy) 2 ](BF 4 ) 2 (terpy=2,2:6′,2′′‐terpyridine) taking advantage of the supramolecular complementarity‐retained low‐temperature fluorescence of the ruthenium center and the SCO behavior of [Fe(dpp) 2 ](BF 4 ) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…These bands are the characteristic absorption bands for monodentataly coordinated CH3COO -ion to the metal ion in all the complexes. Thus on the basis of IR spectra of complexes in comparison to that of the free ligands, it may be asserted that the ligand NBPS acts as bidentate neutral ligand co-ordinating through carbonyl oxygen and azomethine nitrogen while the second ligand NBPTS also The magnetic moment of Fe(II) complexes are found to be 5.07 and 5.08 BM which correspond to high spin octahedral geometry to these complexes [30,31] In these complexes the greater value of DqZ than Dqxy and negative value of Dt conspicuously indicate tetragonal compression along Z-axis in octahedral symmetry.…”
Section: Resultsmentioning
confidence: 99%